Homeomorphism groups of the cube and other n-manifolds - Rolfsen, Dale; Calegari, Danny (My University, 2016)
In this talk, the structure of the homeomorphism group of the cube is presented. Applications to the homeomorphism groups of other n-manifolds are also treated.
Keywords: Grupos de transformaciones; Homeomorphism groups